The Barriers and Facilitators of Self-Management Among Adults with Type 2 Diabetes Mellitus: A Trans Theoretical Model (TTM)-Based Mixed Method Study in Iran - Zare M (Dove Medical Press, 2020)
Maryam Zare,1 Ali Tarighat-Esfanjani,2 Maryam Rafraf,2 Abdolreza Shaghaghi,3 Mohammad Asghari-Jafarabadi,4 Mahmood Shamshiri5 1Department of Nutrition, Khalkhal University of Medical Sciences, Khalkhal, Iran; 2Nutrition Research Center, Faculty of Nutrition and Food Sciences, Tabriz University of Medical Sciences, Tabriz, Iran; 3Department of Health Education and Promotion, Faculty of Health, Tabriz University of Medical Sciences, Tabriz, Iran; 4Road Traffic Injury Research Center, Tabriz University of Medical Sciences, Tabriz, Iran; 5School of Nursing and Midwifery, Ardabil University of Medical Sciences, Ardabil, IranCorrespondence: Ali Tarighat-EsfanjaniNutrition Research Center, Faculty of Nutrition and Food Sciences, Tabriz University of Medical Sciences, Tabriz, 5166614711, IranTel +98-41-33362117Fax +98-41-33340634Email Tarighat45@gmail.comAim: This study planned to determine:( 1) the behavioral intention or profile of patients with type 2 diabetes mellitus (T2DM) based on the stages of the change model, and( 2) to explore the perceived facilitators and barriers of self-management (SM) in a sample of Iranian patients with T2DM.Methods: This was a mixed method study, accomplished in two phases. In the quantitative phase, 246 subjects with T2DM participated. They were classified according to items such as regular use of blood-glucose-lowering drugs, having a healthy diet and performing physical activity to pre-action and action groups. Socio-demographic and anthropometric information were collected, and a phenomenological qualitative study was conducted, and data collection continued until saturation achieved by 10 subjects in pre-action and 12 subjects in action groups. Four focus group discussions in the field of SM were accomplished. Analysis of quantitative and qualitative data was conducted by the SPSS and MAXQDA software, respectively.Results: The mean age and duration of illness among the subjects were 53.9± 7.1 and 6.9± 4.9 years, respectively. The barriers of SM in action and pre-action stages were as follows: lower socio-economic status, poor performance of treatment team, physical-intellectual factors and lack of planning to change. The facilitators stated in the pre-action and action stage in the field of SM were satisfaction from treatment, planning, belief in diabetes, treatment team’s support, nutritional knowledge, and religious beliefs.Conclusion: This study indicated facilitator and barrier factors in SM based on TTM in action and pre-action groups. Healthcare professionals should consider these findings to improve the patients’ outcomes.Keywords: diabetes mellitus type 2, self-management, healthy diet, exercise